RANKING OF RISK FACTORS THAT COULD ACCENTUATE INFECTIOUS DISEASE OUTBREAK IN ADAMAWA STATE, USING ANALYTIC HIERARCHICAL PROCESS (FUDMA JOURNAL OF SCIENCES, 2025)
Disease outbreaks have increased in frequency and scope during the past few decades. The responses to these epidemics have been political and burdensome for disadvantaged groups. Using the Analytic Hierarchy Process (AHP) model, this study is conducted to establish weights to prioritize risk factors that contribute to infectious disease outbreaks in Adamawa State, Nigeria. The following criteria were identified: health policy, finance availability, government commitment to health care, and religious belief. Likewise, potential risk factors were identified as insecurity, poor health infrastructure, permeable borders, access to water, sanitation, and hygiene, poor access to the health care system, illiteracy, local and religious beliefs and poverty. Data collected was analyzed using an AHP model. Poor health infrastructures were placed first, with a weight of 0.1702. A weight of 0.1462 placed illiteracy in second place, indicating that the level of illiteracy ought to be reduced drastically to have a healthy society. With a weight of 0.1445, water, sanitation, and hygiene campaigns should be maintained. Additionally, the spread of infectious diseases was also found to be greatly impacted by insecurity, rated fourth after assessment with 0.1259 weights. Poverty was ranked fifth using the AHP model and was assigned a weight of 0.1115. Poor access to the health care system is ranked sixth with a weight of 0.1072 and religious belief is ranked eighth with a weight of 0.0952. We advised that serious, efficient, and effective action be taken to establish literate citizens.
Keywords: Analytic Hierarchy Process; Risk Factors; Infectious Diseases; Outbreak of Disease